ANALISIS LITERASI EKONOMI PESERTA DIDIK KELAS XI DI MA KHULAFAUR RASYIDIN KUBURAYA - Anggreyni, Febri Rika; Matsum, Junaidi H.; S, Bambang Genjik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to determine: 1) The level of economic literacy of class XI students at MA Khulafaur Rasyidin KUBURAYA, 2) The level of basic economic knowledge of class MA Khulafaur Rasyidin KUBURAYA, 4) Level of understanding of class XI students regarding investment at MA Khulafaur Rasyidin KUBURAYA. The approach used in this research is a quantitative approach with descriptive methods. The population was 47 students taken as a whole to be used as samples. The data collection technique used was a questionnaire. The data analysis used is quantitative descriptive analysis. The research results show that: 1) The economic literacy level of class XI students at MA Khulafaur Rasyidin KUBURAYA is in the agree category with a percentage of 97.9%. 2) The level of basic economic knowledge of class XI students at MA Khulafaur Rasyidin KUBURAYA is included in the disagree category with a percentage of 97.9%. 3) The level of financial understanding and savings of class XI students at MA Khulafaur Rasyidin KUBURAYA is included in the strongly disagree category with a percentage of 100%. 4) The level of understanding about investment of class XI students at MA Khulafaur Rasyidin KUBURAYA is in the strongly disagree category with a percentage of 100%